Questionário de frequência alimentar quantitativo em pacientes com diabetes melito tipo 2 : desenvolvimento e validação de instrumento - Sarmento, Roberta Aguiar (2012)
Objective: To elaborate a quantitative food frequency questionnaire (FFQ) for patients with type 2 diabetes. Design: Dietary data using 3-day weighed diet records (WDR) from 188 outpatients with type 2 diabetes were used to construct the list of usually consumed foods. Foods were initially clustered into eight groups: “cereals, tubers, roots, and derivatives”; “vegetables”; “fruits”; “beans”; “meat and eggs”; “milk and dairy products”; “oils and fats”, and “sugars and sweets”. The frequency of food intake and the relative contribution of each food item to the total energy and nutrient intakes were calculated. A food was included if it contributed at least 80% to total energy or nutrient content in its respective food group. Portion sizes were determined according to the 25th, 50th, 75th, and 95th percentiles of intake for each food item. Setting: GNE - Group of Nutrition in Endocrinology - cohort - Southern Brazil. Subjects: Outpatients with type 2 diabetes. Results: A total of 62 food items were selected based on the 3-day WDR and another 27 foods or their preparation options and nine beverages were included after the expert examination, and accounted for 95% of total energy and nutrient intakes. Also, a portfolio with food photos of each included food item and its portion sizes was created to support the patients in identifying the consumed portion. Conclusions: We developed a practical quantitative FFQ and portfolio with photos of 98 food items covering the past 12 months of the most commonly consumed food items. This dietary method will be valuable to assess the usual diet pattern of patients with type 2 diabetes in Southern Brazil.